Nutritional Status and Dietary Behaviour of Preschool Children in Urban and Rural Settings of Kushtia District (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: The prevalence of child malnutrition in low-income countries appears to be due to a multitude of factors that include inadequate access to enough food and inappropriate dietary practices. Eating pattern of children are known to vary according to socioeconomic position with rural children being known to experience higher levels of socioeconomic disadvantages compared to their urban counterparts. But little is known about the comparative nutritional status and dietary behaviour of the rural and urban preschool children of Bangladesh. The present study was intended to make a comparative evaluation of nutritional status and dietary behaviour of rural and urban preschool children of Bangladesh.Methods: This cross-sectional analytical study was conducted in the Department of Community Medicine, Rajshahi Medical College, Rajshahi with data for the study being collected from the selected urban and rural areas of Kushtia District between January 2020 to December 2020. A total of 450 preschool children (3 to 6 years) whose guardians voluntarily consented to allow them to participate in the study were included. Children with known chronic diseases like valvular heart diseases or any other systemic diseases were excluded. Mothers of the children were the respondents in this study. However, fathers in the absence of mothers served as the respondents. On obtaining ethical clearance from the Ethical Review Committee of Rajshahi Medical College, data were collected from the respondents by face-to-face interview using a semi-structured questionnaire. Anthropometric examination (weight & height) was done using a bathroom scale. World Health Organization’s Child Growth Chart for children < 5 years of age was used as reference for median to compare the nutritional status of the children between urban and rural areas. For analysis, Z-scores was used which was expressed according to weight for age Z-score (WAZ), height for age Z-scores (HAZ), weight for height Z-scores (WHZ) and BMI for age Z-scores (BAZ) as Standard Deviation classification recommended by WHO. Children below -2 SD of the reference median on any of these scales were considered as undernourished and termed as underweight, stunted and wasted respectively. Children below -3 SD were considered severely undernourished. Other parameters were mild undernutrition (-1.99 to -1.00 SD), normal (-0.99 SD to 1 SD), mild overnutrition (1.01-2 SD), moderate overnutrition (2.01-3SD) and severe overnutrition (> 3 SD).Result: The present study revealed that 7% of the rural children were moderate to severely wasted as compared to only 1% of the urban children. However, urban children had a significantly higher prevalence of overweight and obesity (16.4%) compared to their rural counterparts (6.2%). Rural children were more often stunted (6.7% children had moderate to severe stunting) than the urban children (3.1% moderately stunted and none were severely stunted). Rural children were more likely to be underweight (7.1% moderate to severely underweight), than their urban counterparts (1.3% moderate to severely underweight). In terms of BMI for age (BAZ) Z-score urban children were more likely to be overweight and obese (16.4%) than the rural children (6.2%). In general, over 20% of the rural children were undernourished (in terms of wasting, stunting and underweight and BMI for age) compared to over 5% of the urban children. In contrast, over 15% of the urban children were over-nourished (in terms of overweight or obesity) as opposed to over 5% of the rural children. Majority (78.7%) of urban preschool children used to taking breakfast regularly as compared to 62.7% of their rural counterparts. The frequency of taking three major meals a day and light meals 2 or > 2 times a day were significantly higher among urban children compared to that among rural children. Taking fast-food 2-3 times per week was reported to be inappreciably higher in urban cohort than that in rural cohort. About half (49.3%) of the urban children reported taking egg and milk daily as compared to 13 and 15% of the rural children respectively. The proportion of fish and meat consumption was also significantly higher in the former group than that in the latter group. While incidence of taking vegetables was almost identical between two groups of children, having fruits daily was much higher in the urban children than that in the rural children.Conclusion: The study concluded that one in every six rural preschool children is malnourished in terms of wasting stunting and underweight compared to one in every sixteen urban children of similar age and sex. In contrast, one in every six urban children are overweight or obese as opposed to one in every six rural children.Ibrahim Card Med J 2021; 11 (2): 77-83